A Monocity: Revitalization of the Spatial Environment. The Case of Yashkino Urban Settlement in the Kemerovo Region - Klevakin, Alexander; Dolnakov, Petr; Pavlyuchik, Boris (project baikal, 2017)
When the state social-economic system collapsed in the beginning of the 1990s, the necessity to close down the single-industry and subsidized settlements became acute. The settlements failed to survive on their own. It is necessary to establish the investment priorities and to work out the tactics and goals of public and private investments and initiatives. However, the social-economic measures proposed by the government and the Ministry for Economic Development do not come into urban planning practice. The authors propose a conceptual basis for the political course in the urban planning of monocities. Through the case study of the cities of the Kemerovo region they propose possible development scenarios and prove the necessity of intensive use of the spatial environment. The investment sites are marked in the article. It is proposed to integrate the scattered rural sites under the strategy of mixed use, various-story neighborhood development, reconstruction of the former cement factory and its adaptation for a multifunctional center.
Keywords: monocity; Yashkino; quality of spatial environment; strategy of transformation